2016
DOI: 10.1007/s11356-016-6977-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Direct Red 81 mediated by Fenton reactions: multivariate optimization, effect of chloride and sulfate, and acute ecotoxicity assessment

Abstract: The role of different operational parameters related to Fenton reactions (pH, concentration of Fe and HO, and reaction time) and of Cl and SO was investigated in the degradation of the azo dye Direct Red 81, expressed in terms of its decolorization. The factorial design and Pareto's charts showed that only Fe concentration and pH influence the decolorization under the conditions evaluated. So, only these parameters were optimized using the response surface model. Under the best experimental conditions (initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
0
4
0
6
Order By: Relevance
“…36 The complexation of Fe 2+ /Fe 3+ by chloride and sulfate has been observed during degradation of the azo dye Direct Red 81 by Fenton process, causing a decrease in the efficiency of degradation when compared with experiments carried out in the absence of these inorganic anions. 40 Furthermore, Silva et al 7 reported the strong influence of chloride and sulfate on the consumption of H 2 O 2 , extending the time required for the treatment of sanitary landfill leachate by the photo-Fenton process. Meanwhile, no influence of nitrate ions has been observed during the treatment of sanitary landfill leachate using the photo-Fenton process.…”
Section: Resultsmentioning
confidence: 99%
“…36 The complexation of Fe 2+ /Fe 3+ by chloride and sulfate has been observed during degradation of the azo dye Direct Red 81 by Fenton process, causing a decrease in the efficiency of degradation when compared with experiments carried out in the absence of these inorganic anions. 40 Furthermore, Silva et al 7 reported the strong influence of chloride and sulfate on the consumption of H 2 O 2 , extending the time required for the treatment of sanitary landfill leachate by the photo-Fenton process. Meanwhile, no influence of nitrate ions has been observed during the treatment of sanitary landfill leachate using the photo-Fenton process.…”
Section: Resultsmentioning
confidence: 99%
“…• ). 35 Thus, in the STP effluent matrix, the addition of H 2 O 2 is unnecessary. (19) Furthermore, using the optimal experimental conditions for the different aqueous matrices, new experiments were carried out by extending the irradiation time to 240 min for the DW and SW and 360 min for the STP effluent, aiming for higher degradation efficiencies (Figure 3).…”
Section: Influence Of H 2 O 2 Concentrationmentioning
confidence: 99%
“…Este fato, assim como a necessidade de maior tempo de irradiação, demonstra a influência da composição da matriz no processo. LIN, 2017;MARSON et al, 2017;ISMAIL et al, 2018).…”
Section: Avaliação Da Ecotoxicidade Aguda Para a Bactéria Vibrio Fiscunclassified
“…O ânion persulfato (S2O8 2¯) , o qual também pode ser gerado no meio na presença de radicais sulfato (Equação 52), também age como aceptor de elétrons (MARSON et al, 2017;ISMAIL et al, 2018). A adição de um agente oxidante ao meio como o H2O2 também é utilizada para prevenção da recombinação de elétron/ lacuna, uma vez que este reagente também é um forte aceptor de elétrons (AHMED et al, 2011).…”
Section: Avaliação Do Efeito Da Adição De Aceptor De Elétrons (H2o2)unclassified
See 1 more Smart Citation